2007
DOI: 10.1111/j.1447-0594.2007.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in subjective well‐being between ethnic Korean and Japanese elderly residents in an urban community in Japan

Abstract: Background:The ethnic Korean community in Japan has witnessed the increasing aging of their population structure. The purpose of our study was to clarify the differences in standards of living between elderly ethnic Korean and elderly Japanese populations living in Japan, and to examine whether there is any difference in subjective well-being between the two populations. Methods:We conducted a cross-sectional questionnaire-based survey that consisted of items addressing ethnicity, age, gender, literacy, living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Two studies enrolled non-pregnant migrants41 42 and eight exclusively analysed mothers 43–50. The remaining nine studies were of general migrant populations of a single (n=5) or various (n=4) nationalities 51–59. There were 10 studies specifically examining Brazilians of Japanese descent, making them the most studied nation-specific migrant subgrouping in terms of mental well-being 60–70…”
Section: Resultsmentioning
confidence: 99%
“…Two studies enrolled non-pregnant migrants41 42 and eight exclusively analysed mothers 43–50. The remaining nine studies were of general migrant populations of a single (n=5) or various (n=4) nationalities 51–59. There were 10 studies specifically examining Brazilians of Japanese descent, making them the most studied nation-specific migrant subgrouping in terms of mental well-being 60–70…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the evidence suggests female gender, marital status (married) higher education, and income are determinants of PIL. [48] Subjective well being Ottenbacher (2007) [49] Self-acceptance Positive Relation Environmental Mastery Personal Growth Krause (2009) [51] Self-rated Heath/fewer functional disabilities Mortality Ferguson (2010) [52] Optimism Perception of control (mediates relation between optimism and PIL) Hedberg (2010) [53,54]…”
Section: Sociodemographic Determinantsmentioning
confidence: 99%
“…Seven studies (five with low and two with moderate RoB) reported health status to be associated with PIL [26,45,51,60,66,75,80]. Two studies [46,48] showed an association of well-being with PIL and life satisfaction [69,78]. Life satisfaction is a concept that is linked to hedonic well-being [89].…”
Section: Other Determinantsmentioning
confidence: 99%
“…At the level of the individual, Moon and Mikami (2007) studied the association between SWB and literacy using a population of ethnic Korean and Japanese elderly residents in Japan. They used a visual analogue scale to assess SWB and classified participants as illiterate if they answered no to all of the following three questions: ''Are you able to fill out forms for your pension?…”
Section: Literacy and Happinessmentioning
confidence: 99%
“…A search in PsycINFO 1 using keywords ''happiness'' and ''literacy'' produced only five citations (Beckham 1929;Price 2000;Kirkcaldy et al 2004;Lysaker et al 2004;Mindes and Kronenberg 2005), and only one of them actually explored the association between the two constructs. Outside of psychology, related issues have been explored by sociologists (Mwansa 1995) and gerontologists (Moon and Mikami 2007). Other than that, the link appears to be largely unstudied.…”
Section: Introductionmentioning
confidence: 98%